Agroturismo y producción agrícola en la Parroquia San Luis, Cantón Riobamba, Provincia de Chimborazo. - Sánchez Chacaguasay, Deysi Gisela (2024)
ABSTRACT: The present research analyzes the relationship between agrotourism and agricultural production in the San Luis Parish, Riobamba Canton. The methodology used for this research work was documentary, field-based, descriptive, and correlational. Likewise, the research design was non experimental, cross-sectional, and mixed. Likert scale questionnaires were applied to obtain the perceptions of the officials of the San Luis GADP and the inhabitants, thus providing a more precise and broader view of the situation in the locality. The data obtained were analyzed using Cronbach's Alpha statistic to verify the reliability of the instruments. Additionally, IBM SPSS Statistics was used to analyze and interpret results and general and specific hypothesis testing to understand the relationships between the independent and dependent variables thoroughly. Based on the data and results obtained in the research, designing an agrotourism corridor was suggested to increase the development of agrotourism in the San Luis Parish, Riobamba Canton, Chimborazo Province. The name chosen for the tourist corridor is "Yachaks," "Discover the wisdom and power of the Andean